2013
DOI: 10.1186/1477-7819-11-297
|View full text |Cite
|
Sign up to set email alerts
|

High expression of astrocyte elevated gene-1 (AEG-1) is associated with progression of cervical intraepithelial neoplasia and unfavorable prognosis in cervical cancer

Abstract: BackgroundAstrocyte elevated gene-1(AEG-1) plays an important role in the development and progression of certain types of human cancers. However, the expression dynamics of AEG-1 in cervical cancer and its clinical/prognostic significance are unclear.MethodIn present study, the methods of tissue microarrays (TMA) and immunohistochemistry (IHC) were utilized to investigate AEG-1 expression in cervical intraepithelial neoplasia (CIN) and cervical cancer. Receiver operating characteristic (ROC) curve analysis, χ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
(21 reference statements)
2
32
0
Order By: Relevance
“…6,9,10,18,19 In our study, AEG-1 overexpression was found to be significantly associated with lymph node metastasis, parametrial involvement, submucosa stromal invasion, and vascular invasion of CSCC. The results partly accorded with the studies of Huang et al 20 and Long et al 21 Huang et al 20 reported that a high level of AEG-1 correlated with lymphatic metastasis and tumor size of cervical cancer, but they did not present the correlation of AEG-1 with the parametrial involvement, stromal invasion, and vascular invasion of cervical cancer. Long et al 21 reported that AEG-1 was related to the clinical stage of cervical carcinoma.…”
Section: Discussionsupporting
confidence: 88%
“…6,9,10,18,19 In our study, AEG-1 overexpression was found to be significantly associated with lymph node metastasis, parametrial involvement, submucosa stromal invasion, and vascular invasion of CSCC. The results partly accorded with the studies of Huang et al 20 and Long et al 21 Huang et al 20 reported that a high level of AEG-1 correlated with lymphatic metastasis and tumor size of cervical cancer, but they did not present the correlation of AEG-1 with the parametrial involvement, stromal invasion, and vascular invasion of cervical cancer. Long et al 21 reported that AEG-1 was related to the clinical stage of cervical carcinoma.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, multiple studies have suggested that MTDH was associated with tumor invasion and migration. [19][20][21][22][23] We confirmed that MTDH inhibited ESCC cell migration and invasion in vitro, indicating that upregulation of MTDH was significantly associated with metastasis and poorer prognosis of patients with ESCC, which was further verified with meta-analysis carried out on the studies regarding MTDH in SCC. [19][20][21][22][23][24][25][26][27][28] In our meta-analysis, we found that there were significant relationships between MTDH expression in SCC and NAT; SCC tissues with and without lymph node metastasis; clinical stage I and II vs clinical stage III and IV; and T1-T2 vs T3-T4 tissues, [19][20][21][22][23][24][25][26][27][28] which may imply the possibility of using the MTDH expression level as a clinical biomarker of SCC.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, we had meta-analyzed the expression of MTDH in SCC through retrieving the relevant literature. Eventually, the 10 eligible studies 6,11,[19][20][21][22][23][24][25][26] were identified and selected (Table III). MTDH positivity and overexpression were significantly different between SCC and its paired normal 0.53]) (Fig 6, C and D).…”
Section: Resultsmentioning
confidence: 99%
“…AEG-1, which is also called astrocyte elevated gene-1, has been recognized as a key regulator in cancer initiation, development and progression in different types of cancer (28). AEG-1 promoted cell proliferation through the FOXO1/PI3K/AKT signaling pathway in breast cancer (29).…”
Section: Discussionmentioning
confidence: 99%